PELATIHAN DAN PENDAMPINGAN PENGELOLAAN SISTEM PELAPORAN LAPORAN KEUANGAN DAN MANAJEMEN PENGAWASAN KOPERASI - Burhanudin Burhanudin; Nur Khamisah; Aspahani Aspahani; Trie Sartika Pratiwi (COMMENT: Journal of Community Empowerment, 2022)
Cooperatives are business activities that play a role in the process of increasing income, economic growth, and realizing national stability. Cooperative supervisors are elements of the apparatus or cooperative structure other than the meeting of members and cooperative management in Indonesia. It is certain that cooperative performance without supervision will have a negative impact. At least managers find it easy to decide policies. The policy may be ensnared and become a bigger problem. This Community Service activity aims to provide a deeper understanding of the cooperative's financial reporting system and supervisory management, in order to create good and reliable performance management and financial reports. Community service activities are carried out at the PT PUSRI employee cooperative. The activity was attended by 20 cooperative employees. The participants as cooperative supervisors are mostly supervisors who have just been elected and appointed at member meetings in each cooperative unit. Previously the participants did not know about cooperative management, especially in carrying out their duties as supervisors of cooperatives, especially in the field of cooperative accounting in analyzing cooperative finances. However, after evaluating the community service activities, and the results of the evaluation, it was found that employees felt they had gained a better and deeper understanding of the cooperative's financial reporting system.